Phylogenetic systematics of subtribe Spiranthinae (Orchidaceae: Orchidoideae: Cranichideae) based on nuclear and plastid DNA sequences of a nearly complete generic sample - Salazar Chávez, Gerardo Adolfo (2018)
Subtribe Spiranthinae is the most species-rich lineage of terrestrial Neotropical orchids, encompassing > 500 species and 40 genera. We conducted maximum parsimony and maximum likelihood phylogenetic analyses of DNA sequence data of plastid matK-trnK and trnL-trnF and nuclear ribosomal ITS sequences for 36 genera and 182 species of Spiranthinae plus appropriate outgroups. The results strongly support monophyly of Spiranthinae (minus Discyphus, Discyphinae and Galeottiella, Galeottiellinae) and five major lineages, namely monospecific Cotylolabium (sister to the remaining Spiranthinae) and the Eurystyles, Pelexia, Spiranthes and Stenorrhynchos clades. Eighteen of the 27 genera of Spiranthinae for which more than one species was included in our analyses are monophyletic. Paraphyly of large genera, such as Cyclopogon and Sarcoglottis, resulted from segregation of particular species or groups of species exhibiting minor modifications of structures directly involved in pollination (e.g. nectary, rostellum and viscidium). Conversely, polyphyly has resulted from convergent evolution of floral attributes in distantly related species (e.g. Mesadenus). Some of the morphological characters used traditionally for generic delimitation and in nonmolecular cladistic analyses of Spiranthinae are discussed against the evolutionary framework set by our molecular trees, emphasizing putative synapomorphies and problems derived from inappropriate character coding or incorrect homology assessments. Our ancestral area analysis indicates that Spiranthinae originated in eastern South America, with subsequent migrations and secondary radiations in Mesoamerica and North America, plus a derived migration from the latter region to the Old World (Spiranthes).